Homines Religiosi? Expectations and evaluations of Roman sacerdotes in the Late Republic and Early Empire - Antoniou, AA (2022)
This thesis asserts the importance and distinctiveness of sacerdotes and sacerdotia of the Roman republic, drawing principally on late republican and early imperial evidence to elucidate the value and worth of such positions. In focusing on the behaviours, virtues and morals ascribed to these important figures and their collegia, it is demonstrated that being a sacerdos was perceived – by sacerdotes themselves, and by contemporaries, historians, and moralists – to have had an intrinsic importance and distinctiveness which demands identification and explication. This recognition, that being a sacerdos meant more than its political currency, allows us to gain a richer perspective on the worth of these important public figures than is currently appreciated.